Putusnya Perkawinan dengan Alasan Perbuatan Zina Dikaitkan dengan Prinsip Mempersulit Perceraian - Amara Roona Zahira; Bambang Daru Nugroho; Betty Rubiati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The dissolution of a marriage bond due to divorce is a situation that marks the end of the husband and wife relationship in a marriage. Divorce can only be carried out if it is based on strong reasons, as contained in Article 39 paragraph (2), one of which is adultery as in the case of Decision Number 3466/Pdt.G/2021/PA.Dpk. This study aims to analyze and obtain an overview of the implementation of the principle of making divorce difficult in this case and examine the legal protection for the wife of her rights. This research employs a normative juridical approach method with analytical descriptive research specifications, this research consists of two stages, which are library research and field research through literature study research data and interviews. This research employs a qualitative juridical data analysis method. Based on the results of the research, the term “principle of making divorce difficult” is a principle that is applied in the context of an effort to restore the household so that this principle emphasizes that the breakup of marriage due to divorce can only be done, if it has a valid reason, namely the legal reasons contained in the relevant regulations. The dissolution of a marriage due to divorce on the grounds of adultery will certainly have various impacts including negative impacts so that a legal protection is needed for him, in this case one of which is the Judge ex officio according to his position can exercise his rights and authority on matters that are not demanded or requested by the wife such as maintenance.